THE CORRELATION BETWEEN WRITING ESSAY ANXIETY AND WRITING ABILITY OF THE THIRD YEAR ENGLISH STUDY PROGRAM STUDENTS OF UNIVERSITAS RIAU - Mutia Ade Pratiwi; M.Syarfi M.Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was aimed to find out the correlation between writing essay anxiety and writing ability of the third year English Study Program Students of Universitas Riau. The population of this research was 113 students which divided into 5A, 5B and 5C class as total number of the third year English Study Program Students of Universitas Riau. The researcher used cluster random sampling to choose the sample and 5C class had been chosen as the sample of the research which was made up of 36 students. The researcher used a questionnaire and a test to collect the data. There were 27 items for questionnaire of writing essay anxiety. The second instrument was a writing test. The researcher prepared 3 topics and students chose one topic and wrote an essay for at least 200 words. The result of writing test was checked by 3 raters. The researcher used SPSS to find out the correlation of the research. The result showed that there is a significant correlation between students’ writing anxiety and students’ writing ability of the third-year students of English Study Program by number of 0.717 which is between 0.70 and 0.90. According to Sugiyono (2017) it can be concluded that the students’ writing essay anxiety and students’ writing ability of this research has a strong positive correlation.Key Words: Correlation, Essay, Anxiety